Migration and Reallocation of Educational Resources in China – From the Perspective of Educational Resource Capacity (Asian Education Studies, 2017)
The massive rural-to-urban migration, which tends to occur more frequently in family units, has caused increasing children to follow their migrant parents to cities. The surges of migrant children relocating to cities trigger a strong demand for compulsory education for migrant children in migrant inflow cities and raise challenges for capacity of urban educational resources. This study discovers that China suffers from a severely unequal distribution of educational resources across different regions as well as a significant imbalance between supply and demand of education. The allocation of educational resources is subject to the capacity of education supply. Based on a review of the population distribution and the trend of recent migration in China, an analysis is conducted to simulate migrant children’s migration behavior. The analysis results imply that the flow of the demand for education caused by the migrant children benefits the maintenance of an equitable education system. It is recommended that regional supplemental education solutions be identified in migrant outflow regions. It is encouraged that migrant outflow regions make more effort to accommodate migrant children. More specifically, it is encouraged to make more flexible and customized distribution of educational resources so that an allocation mechanism suitable for the massive rural-to-urban migration can be established.